PENGARUH VARIASI KONSENTRASI GUM ARABIC TERHADAP NILAI SOLID CONTENT PADA TINTA ORGANIK BERBASIS PIGMEN ARANG TEMPURUNG KELAPA - Farhan Mulya; Heribertus Rudi Kusumantoro; Rachmah Nanda Kartika (Universitas Samudra, 2026)
The development of the printing industry has increased the demand for environmentally friendly inks as an alternative to petroleum-based inks. One potential approach is the utilization of coconut shell charcoal as a carbon pigment source and gum arabic as a natural binder in organic ink formulations. This study aimed to analyze the effect of varying gum arabic concentrations on the solid content of organic ink based on coconut shell charcoal pigment. A quantitative experimental method was employed in this research. Ink samples were formulated using two pigment bases, namely ethanol and distilled water, with gum arabic concentrations of 1%, 3%, 5%, 7%, and 9%. Solid content testing was conducted using the gravimetric method by drying the samples at 105°C until a constant weight was achieved. The results indicated that increasing the concentration of gum arabic led to higher solid content values in both pigment-base formulations. The ethanol-based samples exhibited an increase in solid content from 6.73% to 13.61%, while the distilled water-based samples increased from 6.06% to 14.86%. The highest solid content value was obtained in sample AT-5 containing 9% gum arabic. These findings demonstrate that gum arabic concentration has a positive effect on the solid content of organic ink, indicating its potential to improve ink quality in terms of solid composition and printing performance.